1989
DOI: 10.1099/0022-1317-70-1-187
|View full text |Cite
|
Sign up to set email alerts
|

A Cytopathological Investigation of Autographa californica Nuclear Polyhedrosis Virus p10 Gene Function Using Insertion/Deletion Mutants

Abstract: SUMMARYThe role of the Autographa cali]brniea nuclear polyhedrosis virus pl0 gene in viral cytopathology and morphogenesis was examined using classes of pl 0 deletion mutants with and without lacZ (fl-galactosidase) gene fusion. Mutant-infected cells did not form the fibrillar cytoplasmic and nuclear structures normally observed late in infection with wild-type (wt) virus, and the cells failed to lyse even at 2 weeks post-infection. Based on wt and mutant cytopathology, we suggest lysis may be facilitated by s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
103
0
7

Year Published

1989
1989
2010
2010

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 143 publications
(112 citation statements)
references
References 20 publications
2
103
0
7
Order By: Relevance
“…This extensive concentration of the PE protein at the periphery of pl0 structures may be due to the lack of polyhedra which would normally provide a substrate for PE protein deposition in wt OpMNPV-infected cells. In combination with the observation that pl0-minus recombinant AcMNPV lacks or forms an incomplete polyhedron envelope (Vlak et al, 1988;Williams et al, 1989), these immunoelectron microscopic data indicate the presence of a functional relationship between pl0 and the PE protein. It is likely that pl0 plays a role in the assembly and proper association of the PE protein with polyhedra.…”
Section: Pio : Cross-reaction Of the Plo Mab With A Cellular Proteinmentioning
confidence: 57%
See 1 more Smart Citation
“…This extensive concentration of the PE protein at the periphery of pl0 structures may be due to the lack of polyhedra which would normally provide a substrate for PE protein deposition in wt OpMNPV-infected cells. In combination with the observation that pl0-minus recombinant AcMNPV lacks or forms an incomplete polyhedron envelope (Vlak et al, 1988;Williams et al, 1989), these immunoelectron microscopic data indicate the presence of a functional relationship between pl0 and the PE protein. It is likely that pl0 plays a role in the assembly and proper association of the PE protein with polyhedra.…”
Section: Pio : Cross-reaction Of the Plo Mab With A Cellular Proteinmentioning
confidence: 57%
“…In addition, a hyperexpressed protein, pl0, has been found associated with polyhedra (Quant- Russell et al, 1987) and also with the fibrillar structures (Vlak et al, 1988). P10 appears to play a role in the proper assembly of polyhedra, as it has been demonstrated that p 10-minus virus recombinants produce polyhedra which are unstable and readily fracture (Williams et al, 1989), with polyhedron envelopes that are incomplete or absent (Vlak et al, 1988;Williams et al, 1989). The p39 protein is a component of the virion nucleocapsid and is one of the major proteins occluded within polyhedra (Pearson et al, 1988;Thiem & Miller, 1989).…”
Section: Introductionmentioning
confidence: 99%
“…A second protein, p10, is produced at high levels and is associated with the formation of large fibrillar structures in both the nuclei and cytoplasm of infected cells (van der Wilk et al, 1987 ;Quant-Russell et al, 1987 ;Vlak et al, 1988). Studies with p10 deletion mutants of Autographa californica (Ac) MNPV have revealed that intact p10 is also involved in nuclear disintegration and in polyhedron morphogenesis (Williams et al, 1989 ;van Oers et al, 1993). However, p10 was not essential for virus replication and infection of insect cells with a p10-deleted virus could produce occlusion bodies (Williams et al, 1989).…”
Section: Introductionmentioning
confidence: 99%
“…Studies with p10 deletion mutants of Autographa californica (Ac) MNPV have revealed that intact p10 is also involved in nuclear disintegration and in polyhedron morphogenesis (Williams et al, 1989 ;van Oers et al, 1993). However, p10 was not essential for virus replication and infection of insect cells with a p10-deleted virus could produce occlusion bodies (Williams et al, 1989). These features suggest the p10 promoter as a suitable site for cloning and the effective production of large quantities of heterologous proteins in insect cells, as demonstrated by expression of the cauliflower mosaic virus gene I (Vlak et al, 1990), and as described by Miller (1993) and O'Reilly et al (1994).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, it has been shown that the non-structural pl0 protein, which is synthesized at levels similar to those of polyhedrin throughout the very late phase of infection, also is not essential for virus replication (Vlak et al, 1988). The pl0 promoter has been utilized to construct expression vectors in which the foreign coding sequences replace those of the pl0 gene within the viral genome (Vlak et al, 1988;Williams et al, 1989;Vlak et al, 1990). Furthermore, it has been shown that the pl0 promoter can also function at a different location within virus DNA.…”
Section: Introductionmentioning
confidence: 99%